A lysosome-targeted near-infrared fluorescent probe for imaging endogenous cysteine (Cys) in living cells. Issue 11 (26th February 2020) - Cai, Songtao; Liu, Chang; Jiao, Xiaojie; Zhao, Liancheng; Zeng, Xianshun
Abstract : A lysosome-targeted near-infrared (NIR) fluorescent probe SHCy-C for detecting and imaging endogenous Cys in living cells has been developed. Abstract : Cysteine (Cys) is one of the most important essential biothiols in lysosomes. Highly selective probes for specific detection and imaging of lysosomal Cys over other biological thiols are rare. Herein, we developed a lysosome-targeted near-infrared fluorescent probe SHCy-C based on a novel NIR-emitting thioxanthene–indolium dye. Due to the turn-on fluorescence response elicited by the intramolecular charge transfer (ICT) processes before and after the reaction with Cys, probe SHCy-C exhibits high selectivity and sensitivity (16 nM) for the detection of Cys. More importantly, probe SHCy-C is found to precisely target lysosomes and achieves the "turn-on" detection and imaging of endogenous Cys in lysosomes.